Utility-optimized bandwidth and power allocation for non-orthogonal multiple access in software defined 5G networks. (1st July 2018) - Huang, Xiaohong; Yuan, Tingting; Zhang, Yan
Abstract: The fifth Generation (5G) wireless network will be in very high carrier frequencies with massive bandwidths, extreme base stations and device densities. For optimization of 5G network, it is of vital importance to design end to end resource allocation mechanism across the radio access network and core network. In this paper, we propose an algorithm for joint resource optimization across wireless links and core networks. Our goal is twofold. First, Non-Orthogonal Multiple Access (NOMA) technique is considered for performance enhancement in 5G network, and Software Defined Network (SDN) technique is considered for resource allocation in core network. Second, the joint network utility optimization algorithm with multipath is proposed through proper power allocation across access network in conjunction with bandwidth allocation across core network, in which utility is an important indicator to reflect the level of user or application satisfaction and fairness of the allocated bandwidth. Extensive simulation has been done to evaluate the performance of proposed algorithm. The results show that the proposed joint optimization algorithm is able to achieve significant improvement in terms of network utility with more SDN devices deployed. Highlights: End to end resource allocation for software defined 5G network with multipath. A utility optimization model jointly considering access network and core network. Problem decomposition method is used to solve the joint optimization problem. Hybrid SDN is tested to show the influence of SDN deployment ratio on utility.